Ultramicronized Palmitoylethanolamide and Luteolin Supplement Combined with Olfactory Training to Treat Post-COVID-19 Olfactory Impairment: A Multi-Center Double-Blinded Randomized Placebo- Controlled Clinical Trial - DI STADIO, Arianna; D’ASCANIO, Luca; VAIRA, Luigi Angelo; CANTONE, Elena; DE LUCA, Pietro; CINGOLANI, Cristina; MOTTA, Gaetano; DE RIU, Giacomo; VITELLI, Federica; SPRIANO, Giuseppe; DE VINCENTIIS, Marco; CAMAIONI, Angelo; et al. (Current neuropharmacology, 2022)
Background: Olfactory training is the only evidence-based treatment for post-viral olfactory dysfunction. Smell disorders after SARS-CoV-2 infection have been attributed to neuroinflammatory events within the olfactory bulb and the central nervous system. Therefore, targeting neuroinflammation is one potential strategy for promoting recovery from post-COVID-19 chronic olfactory dysfunction. Palmitoylethanolamide and luteolin (PEA-LUT) are candidate antiinflammatory/ neuroprotective agents. Objective: To investigate recovery of olfactory function in patients treated with PEA-LUT oral supplements plus olfactory training versus olfactory training plus placebo. Methods: Multicenter double-blinded randomized placebo-controlled clinical trial was held. Eligible subjects had prior COVID-19 and persistent olfactory impairment >6 months after follow-up SARS-CoV-2 negative testing, without prior history of olfactory dysfunction or other sinonasal disorders. Participants were randomized to daily oral supplementation with ultramicronized PEA-LUT 770 mg plus olfactory training (intervention group) or olfactory training with placebo (control). Sniffin Sticks assessments were used to test the patients at baseline and 90 days. Results: A total of 185 patients, including intervention (130) and control (55) were enrolled. The intervention group showed significantly greater improvement in olfactory threshold, discrimination, and identification scores compared to controls (p=0.0001). Overall, 92% of patients in the intervention group improved versus 42% of controls. Magnitude of recovery was significantly greater in the intervention group versus control (12.8 + 8.2 versus mean 3.2 + 3), with >10-fold higher prevalence of anosmia in control versus intervention groups at the 90-day endpoint. Conclusion: Among individuals with olfactory dysfunction post-COVID-19, combining PEA-LUT with olfactory training resulted in greater recovery of smell than olfactory training alone.